2008
DOI: 10.1016/j.jnutbio.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Protein–energy malnutrition increases activation of the transcription factor, nuclear factor κB, in the gerbil hippocampus following global ischemia☆

Abstract: Protein-energy malnutrition (PEM) exacerbates functional impairment caused by brain ischemia. This is correlated with reactive gliosis, which suggests an increased inflammatory response. The objective of the current study was to investigate if PEM increases hippocampal activation of nuclear factor κB (NFκB), a transcription factor that amplifies the inflammatory response involved in ischemic brain injury. Mongolian gerbils (11-12 weeks old) were randomly assigned to control diet (12.5% protein) or protein-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The nonsteroidal GW3965, a LXR full agonist on both LXRα and LXRβ, (Collins et al, 2002) can cross the blood-brain barrier and exert specific actions on LXR receptors. In this study we therefore investigated whether LXR agonist can protect the brain through reducing NF-κB, activated after global ischemic insult (Ji et al, 2008;Rehni et al, 2009;Webster et al, 2009). We have found that LXR agonist has no effect on the phosphorylated IκBα, the major inhibitor of NF-κB (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The nonsteroidal GW3965, a LXR full agonist on both LXRα and LXRβ, (Collins et al, 2002) can cross the blood-brain barrier and exert specific actions on LXR receptors. In this study we therefore investigated whether LXR agonist can protect the brain through reducing NF-κB, activated after global ischemic insult (Ji et al, 2008;Rehni et al, 2009;Webster et al, 2009). We have found that LXR agonist has no effect on the phosphorylated IκBα, the major inhibitor of NF-κB (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic malnutrition has been reported to impair the ability to maintain thermoregulatory homeostasis [16][17][18], especially when animals are confronted with thermoregulatory challenges [17]. Therefore, an altered thermoregulatory response induced by PEM could explain some of the changes in the neuronal and glial response following global ischemia previously reported by our laboratory [10,11].…”
Section: Introductionmentioning
confidence: 75%
“…Clinical evidence, with noted methodological limitations, has demonstrated a correlation between PEM and increased morbidity and mortality following stroke [3][4][5]9]. A cause-and-effect relationship has been identified with the use of a rodent model of global brain ischemia demonstrating that PEM affects outcome on both a cellular and functional level [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…While clinical studies have focused on the relationship between nutritional status and infection rates, length of hospital stay [8], and muscle strength [11], we identified direct effects on the ischemic brain. In rodent models of global brain ischemia mimicking the clinical scenario of PEM pre-existing at the time of ischemia and continuing untreated, PEM appeared to lower the set-point for the inflammatory response in the vulnerable hippocampal CA1 subregion [10], [12]. This was evident as an increase in activation of the predominant pro-inflammatory transcription factor, nuclear factor kappa B [12], and, in a subset of malnourished rodents, an augmented glial response to global brain ischemia [10].…”
Section: Introductionmentioning
confidence: 99%
“…In rodent models of global brain ischemia mimicking the clinical scenario of PEM pre-existing at the time of ischemia and continuing untreated, PEM appeared to lower the set-point for the inflammatory response in the vulnerable hippocampal CA1 subregion [10], [12]. This was evident as an increase in activation of the predominant pro-inflammatory transcription factor, nuclear factor kappa B [12], and, in a subset of malnourished rodents, an augmented glial response to global brain ischemia [10]. While pre-existing PEM did not exacerbate neuronal death, neuroplasticity-related proteins were altered [10], [13].…”
Section: Introductionmentioning
confidence: 99%